Assessing National Discourse and Local Governance Framing of Climate Change for Adaptation in the United Kingdom. Issue 4 (4th July 2017) - Romsdahl, Rebecca J.; Kirilenko, Andrei; Wood, Robert S.; Hultquist, Andy
ABSTRACT: While many national governments struggle to maintain global climate change as a high priority issue, many local governments are taking action to fill the policy gaps. This study examines how local governments across the United Kingdom of Great Britain are reframing climate change. We compiled a dataset of newspaper publications covering climate change over a 10-year timeframe, plus survey and interview responses from local governance practitioners, to identify a shift in national discourse that has changed the priority level of climate change in UK local governance. This paper argues that many local governments are strategically reframing climate change as alternative issues in order to make progress in climate adaptation planning.